2019
DOI: 10.5897/ajbm2019.8766
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity, non-executive directors composition and corporate performance: evidence from listed firms in Nigeria

Abstract: This paper examined the nexus between board gender diversity, non-executive director's composition and corporate performance (return on asset) of listed firms on the Nigerian Stock Exchange. Ex-post facto research design was employed and agency theory formed the basis of theoretical framework of the study. Data of board gender diversity, non-executive director's composition and return on asset were obtained for seventy-two listed firms during the period 2006 to 2016. The data obtained were analyzed by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…According to Robbins & Decenzo [62], Board gender diversity depicts the varied personal characteristics that make the workforce heterogeneous. According to Imade [34], board gender diversity is part of board diversity. It refers to the difference in the number of women on the Board of corporate firms.…”
Section: Board Gender Diversity and Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Robbins & Decenzo [62], Board gender diversity depicts the varied personal characteristics that make the workforce heterogeneous. According to Imade [34], board gender diversity is part of board diversity. It refers to the difference in the number of women on the Board of corporate firms.…”
Section: Board Gender Diversity and Advantagesmentioning
confidence: 99%
“…Imade [34] researched board gender diversity among 72 quoted companies on the Nigerian stock exchange between 2006 and 2016; the results revealed that board gender diversity has a significant effect on corporate performance (Return on Asset) quoted companies Nigerian stock exchange. Temile, Jatmik &Hidayat [72], examined the impact of gender diversity, earnings management practices and quoted companies' corporate performance in Nigerian.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Imade [20] examined the nexus between board gender diversity, non-executive director's composition and corporate performance (return on asset) of listed firms on the Nigerian Stock Exchange. Ex-post facto research design was employed and agency theory formed the basis of theoretical framework of the study.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The ratio assesses the efficiency of using company assets to generate income. The prior literature widely analyzes ROA to investigate the effects of SB structure and composition on company financial performance (Boadi and Osarfo, 2019;Imade, 2019;Jakpar et al, 2019;Jentsch, 2019;Abdeljawad and Masri, 2020). Moreover, ROA can indicate the quality of corporate governance in inspiring higher management effectiveness.…”
Section: Return On Assetsmentioning
confidence: 99%